Símbolos y ritos andinos: un intento de comparación con el área vecina amazónica - Ortiz Rescaniere, Alejandro (1985)
Some considerations on the risks of analysis of the mythical Andean texts. An enriching suggestion: try comparisons between myths of the cultural areas of the Andes and the western Amazon. This article ends by showing the possibilities of the proposed comparison through a brief analytical essay that compares myths from both regions.